Verbs with the Prefix za- in Russian dialects of the Amur Region - V. T. Sadchenko (Научный диалог)
The article deals with verb derivatives with the prefix za- on the dialectal material that is poorly studied in this aspect — the Russian dialects of the Amur region. The derivational and grammatical meanings of the derived verbs with this formant are characterized in comparison with their literary counterparts. The peculiarities of semantics are revealed and a typology of dialectisms with this prefix is proposed. It is concluded that word formation in this group of dialects is a peculiar form of manifestation of specific and general Russian word-formation tendencies. The relevance and novelty of the work is due to both the general unresolved problem of describing the meanings of Russian verb prefixes, and insufficient knowledge of the specifics of verbal word formation in dialects. In addition, the study of this group of dialects in the derivational aspect is necessary for the construction of a typology of dialects of the Far East and the preparation of a monographic description of them. Turning to the study of prefix verb dialect lexicon can contribute to the introduction of new interesting facts into scientific circulation. Turning to dialects of secondary education, which are under the strongest influence of the literary language, can help to reveal the dynamics of transformations of prefixed meanings.